2007
DOI: 10.1002/jssc.200700110
|View full text |Cite
|
Sign up to set email alerts
|

Rapid HPLC analysis of the antiepileptic lamotrigine and its metabolites in human plasma

Abstract: A liquid chromatographic method with diode array detection (DAD) has been developed for the analysis of the antiepileptic agent lamotrigine (LTG) and its metabolites, lamotrigine 2-N-glucuronide and 2-N-methylated in plasma samples. The analytes were separated on a C8 RP column, using a mobile phase composed of methanol and a 0.45 mM, pH 3.5 phosphate buffer containing 0.17% triethylamine (24:76 v/v). Melatonin was used as the internal standard (IS). The DAD detector was set at 220 nm for the detection of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 20 publications
1
19
0
1
Order By: Relevance
“…Only a few papers describe the determination of LMT and its metabolites in biological fluids by means of HPLC with DAD detection [195], electrokinetic chromatography (MEKC) [205], Automated Sequential Trace Enrichment of Dialysates HPLC [206] and HPLC mass spectrometry [196]. The pre-treatment of biological samples is usually carried out by means of deproteinization by solvents [186,187,196], liquid-liquid extraction [185], solid phase extraction (SPE) [188,205] and solid phase micro-extraction (SPME) [200] procedures.…”
Section: Methods Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few papers describe the determination of LMT and its metabolites in biological fluids by means of HPLC with DAD detection [195], electrokinetic chromatography (MEKC) [205], Automated Sequential Trace Enrichment of Dialysates HPLC [206] and HPLC mass spectrometry [196]. The pre-treatment of biological samples is usually carried out by means of deproteinization by solvents [186,187,196], liquid-liquid extraction [185], solid phase extraction (SPE) [188,205] and solid phase micro-extraction (SPME) [200] procedures.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Few studies can be found in the literature regarding the determination of LMT as a single analyte or together with other drugs or its metabolites in biological fluids by means of HPLC with UV (or diode array) [107,[185][186][187][188][189][190][191][192][193][194][195], or mass spectrometry [196][197][198] detection and by means of gaschromatography (GC) [199][200][201] or capillary electrophoresis (CE) methods [202][203][204][205]. Only a few papers describe the determination of LMT and its metabolites in biological fluids by means of HPLC with DAD detection [195], electrokinetic chromatography (MEKC) [205], Automated Sequential Trace Enrichment of Dialysates HPLC [206] and HPLC mass spectrometry [196].…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Compared with human clinical cases, the LTG administration period was shorter than the clinical occurrence period (1 day vs. 2 weeks), and the plasma C max LTG exposure level (Table ) was 3‐ to 46‐fold higher than the steady‐state plasma level in humans (4‐60 μ m ) (Saracino et al, ; Sauve et al, ), suggesting that acute progression of hepatotoxicity in mice would be partly responsible for the differences of liver histopathological change between human and mice. BSO‐mediated GSH depletion model could be applied short‐term toxicity study, since 2‐3 weeks repeated BSO administration caused mitochondrial damage in muscle (Martensson & Meister, ).…”
Section: Discussionmentioning
confidence: 99%
“…About 30 μL blood was collected from the jugular vein without anesthesia at 0.5, 1, 2, 12 and 24 hours after LTG administration. Plasma concentrations of LTG were measured using a high‐performance liquid chromatography (HPLC) method described previously (Saracino, Bugamelli, Conti, Amore, & Raggi, ) with a slight modification. In brief, 10 μL of plasma was mixed with 90 μL of acetonitrile and centrifuged at 4°C, 12 000 g for 10 minutes, and the resulting supernatants were injected into HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…É eficaz no tratamento de crises epilépticas generalizadas e focais, no tratamento adjunto da epilepsia refratária (PUCCI et al, 2005;KIM et al, 2015), pode ser empregada como estabilizador de humor em pacientes com transtorno bipolar (SARACINO et al, 2007;MORGAN et al, 2011;KIM et al, 2015;NIKOLAOU et al, 2015) e no tratamento da síndrome de Lennox-Gastaut (KIM et al, 2015;MOSHÉ et al, 2015). Além disso, estudos demonstraram que a LTG pode ser eficaz no tratamento a dependência de cocaína, álcool e inalantes (ZALEWSKA-KASZUBSKA et al, 2015).…”
Section: Lamotriginaunclassified